Global trends of antibiotics research: comparison using network analysis to map the tendencies of antibiotics in water, soil and sediment - ZHENG, Chunli; LIAO, Hongkai; TU, Chenglong (Earth and environmental science transactions of the Royal Society of Edinburgh, 2021)
Antibiotic residues have entered into the environment owing to the unreasonable use and disposal of antibiotics. The emergence of antibiotic resistance poses a huge threat to ecosystems and human health. In this study, the network analysis method was used to compare publications on antibiotics in water, soil and sediment from the aspects of countries, institutes, journals, subject categories and keywords based on Web of Science Core Collection. The results indicated that the United States of America and China had dominant positions of studies on antibiotics. The Chinese Academy of Sciences published the most articles on antibiotic research. ‘Chemosphere’, ‘Science of the Total Environment’, ‘Environmental Science and Technology’ and ‘Applied and Environmental Microbiology’ all appeared in the top six journals. ‘Environmental Sciences and Ecology’ was the core subject category of antibiotic research. Further analysis results depicted that ‘Antibiotics’, ‘Tetracycline’ and ‘Antibiotic Resistance’ were found as the research hotspots. Tetracycline and oxytetracycline all showed in the top 50 keywords of antibiotics research in water, soil and sediment. However, chlortetracycline, sulfadiazine and tylosin all emerged only in the top 50 keywords of antibiotics study in soil. In future, more attention should be paid to antibiotic resistance genes and antibiotic resistance bacteria in antibiotics research.